Public perception and attitude towards chemical industry park in Dalian, Bohai Rim. (April 2018) - He, Guizhen; Chen, Chunci; Zhang, Lei; Lu, Yonglong
Abstract: Recent decade has witnessed accelerating expansion of chemical industry and increasing conflicts between the local citizens, governmental authorities and project developers, especially in some coastal and port cities in China. Development and transformation of chemical industrial parks has been adopted as a national initiative recently. However, there is a paucity of research examining public perspectives on chemical industrial parks and their risks. Aiming to understand public perception, attitude, and response and the factors underlying the support/acceptance of chemical industry park, this paper investigated 418 residents neighboring to two chemical industrial parks, Dalian in Bohai Rim through face-to-face questionnaire survey. The results showed the knowledge of the respondents on the chemical industrial parks development was very limited. The respondents had complex perceptions on the environmental impacts, risks control, social-economic benefits, and problem awareness. The current levels of information disclosure and public participation were very low. The central governmental official (44.3%) was the most trustworthy group by the respondents. Only 5.5% and 23.2% of the respondents supported the construction of a new CIP nearby and far away their homes, whilst 13% thought new CIP project as acceptable. The spearman correlation analysis results showed a strong NIMBY effect (Not In My Backyard). Factor analysis results demonstrated five latent factors: knowledge, benefit, information, trust, and participation. Multiple linear regression analysis indicated how socio-demographic differences and five latent factors might impact on the support/acceptance of the chemical industrial parks. Education level, trust, information, and participation were significant predictors of public support/acceptance level. This study contributes to our limited knowledge and understanding of public sentiments to the chemical industry parks in China. Highlights: Chemical industrial park development and strategy is provided. Knowledge level of the respondents was very limited. Public perceptions, attitudes, and responses of chemical industrial park are illuminated. Five key factors of public acceptance of chemical industrial park are identified. Abstract : Local residents' perceptions, attitudes, responses, and main factors underlying the acceptance of chemical industry parks were investigated and studied.